Intercalations and Characterization of Zinc/Aluminium Layered Double Hydroxide-Cinnamic Acid - Nurain Adam; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Nur Nadia Dzulkifli; Cik Rohaida Che Hak; Siti Halimah Sarijo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Cinnamic acid (CA) is known to lose its definite function by forming into radicals that able to penetrate into the skin and lead to health issues. Incorporating CA into zinc/aluminum-layered double hydroxides (Zn/Al-LDH) able to reduce photodegradation and eliminate close contact between skin and CA. Co-precipitation or direct method used by using zinc nitrate hexahydrate and aluminium nitrate nonahydrate as starting precursors with addition of various concentration of CA. The pH were kept constant at 7 ± 0.5. Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR) shows the presence of nanocomposites peak 3381 cm–1 for OH group, 1641 cm–1 for C=O group, 1543 cm–1 for C=C group and 1206 cm–1 for C–O group and disappearance of N–O peak at 1352 cm–1 indicates that cinnamic acid were intercalated in between the layered structures. Powder X-Ray Diffraction (PXRD) analysis for Zn/Al-LDH show the basal spacing of 9.0 Ǻ indicates the presence of nitrate and increases to 18.0 Ǻ in basal spacing in 0.4M Zn/Al-LDH-CA. CHNS analysis stated that 40 % of cinnamic acid were being found and intercalated in between the interlayer region of the Zn/Al-LDH with higher thermal stability. Field Emission Scanning Electron Microscope (FESEM) images of 0.4 M Zn/Al-LDH-CA shows that the nanocomposites are in more compact, flaky non porous, large agglomerates with smooth the surfaces of the intercalated compound. Controlled release was successful with 80 % release in phosphite anion and 70 % release carbonate anion. The cinnamic acid was successfully inserted between the interlayer regions of Zn/Al-LDH with slow release formulation.